Diesel exhaust exposure intensifies inflammatory and structural changes associated with lung aging in mice - Ribeiro Júnior, Gabriel; de Souza Xavier Costa, Natália; Belotti, Luciano; dos Santos Alemany, Adair Aparecida; Amato-Lourenço, Luís Fernando; da Cunha, Paula Gabriela; de Oliveira Duro, Stephanie; Ribeiro, Susan Pereira; Veras, Mariana Matera; Quirino dos Santos Lopes, Fernanda Degobbi Tenorio; Marcourakis, Tania; Nascimento Saldiva, Paulo Hilário; et al. (Ecotoxicology and environmental safety, 2019)
Life expectancy is increasing worldwide. Lung aging is a process marked by changes in multiple morphological, physiological and age-related biomarkers (e.g., sirtuins) and is influenced by external factors, such as air pollution. Hence, the elderly are considered more vulnerable to the air pollution hazards. We hypothesized that diesel exhaust (DE) exposure intensifies changes in lung inflammatory and structural parameters in aging subjects. Two- and fifteen-month-old mice were exposed to DE for 30 days. Lung function was measured using the forced oscillation method. The inflammatory profile was evaluated in the bronchoalveolar lavage fluid (BALF) and blood, and lung volumes were estimated by stereology. Antioxidant enzyme activity was evaluated by spectrophotometry, sirtuin 1 (SIRT1), sirtuin 2 (SIRT2) and sirtuin 6 (SIRT6) expression was assessed by reverse transcription polymerase chain reaction (RT-PCR), and levels of the sirtuin proteins were evaluated by immunohistochemical staining in lung tissues. Older mice presented decreased pulmonary resistance and elastance, increased macrophage infiltration and decreased tumor necrosis factor (TNF) and interleukin 10 (IL-10) levels in the BALF, reduced activities of the antioxidant enzymes glutathione peroxidase (GPx) and glutathione reductase (GR), and increased activity glutathione S-transferase (GST); increased lung volumes with decreased elastic fiber and increased airway collagen content. SIRT1 gene expression was decreased in older animals, but protein levels were increased. DE exposure increased macrophage infiltration and oxidative stress in the lungs of animals of both ages. SIRT6 gene expression was decreased by DE exposure, with increased protein levels. In older animals, DE affected lung structure and collagen content. Lung aging features, such as decreased antioxidant reserves, lower IL-10 expression, and decreased SIRT1 levels may predispose subjects to exacerbated responses after DE exposure. Our data support the hypothesis that strategies designed to reduce ambient air pollution are an important step towards healthy aging. [Display omitted] •DE exposure accelerates lung aging in mice.•DE exposure decreases the mRNA expression and increases protein expression of SIRT6 in the lung regardless of the mice age.•Anti-oxidant enzymes imbalance occurred due to DE exposure in old and young mice.•Morphological/structural changes and increased collagen content occurred due to DE exposure only in the lungs of aged mice.